PERAN AKTIVITAS PEMASARAN MEDIA SOSIAL DALAM MENINGKATKAN LOYALITAS MEREK - Nurhadi, Mochamad; Ramadhani, Hanif; Ronny, Ronny (Buletin Studi Ekonomi, 2025)
This research aims to analyze the structural model of social media marketing in increasing customer loyalty through loyalty, trust and brand awareness of SME Kopi Kenangan products in Indonesia. The research population involved Kopi Kenangan customers in big cities, with data collected from 157 respondents via a Google Form questionnaire using a purposive sampling technique. Variables were measured using a Likert scale, and data analysis was carried out using PLS-SEM through evaluation of measurement and structural models. The results of the study indicate that social media marketing activities do not directly increase brand loyalty in Kopi Kenangan SMEs in Indonesia. The role of brand awareness and brand image in mediating the influence of social media marketing activities in increasing consumer loyalty is substantial. Social media marketing activities influence brand awareness, brand image, and brand trust. Likewise, brand awareness and brand image have a positive influence on brand loyalty, but brand trust does not affect brand loyalty.